ANALISIS DIAMETER PIPA PDAM SEBAGAI JALUR TRANSMISI SINYAL WI-FI PADA FREKUENSI 2.4 GHZ - Susanti H. Hasan; Yono Hadi Pramono (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Have performed the analysis of metal pipe PDAM as transmission line wave had Wi-Fi at a frequency of 2.4 GHz. The method of attenuation measurements with observations on a variety of pipe diameters. The setting is done by using an access point as a Wi-Fi transmitter through monopole antenna. So also on the type of receiver used monopole antenna. To optimize Wi-Fi radiation in order to fully enter into the pipe, then use the box as a Faraday cage conductor who will wrap up a second access point both at the transmitter and receiver. From the analysis of the pipe diameter PDAM to a diameter of 3 inches (7.65 cm) loss / attenuation of 13.61 dBm, to a diameter of 4 inches (10.16 cm) loss / attenuation of 13.02 dBm, and for a diameter of 6 inches (15.24 cm) loss / attenuation of 1.66 dBm. Compared with without using the pipe as a transmission line for the same distance of 3 meters loss / attenuation reaches 56.1 dBm. Overall results of this study will be useful for people to get a Wi-Fi signal communication via pipeline PDAM. Keyword : Wi-Fi, Monopole Antenna, Wave Transmission, Attenuation.